Do Brazil's Covid-19 government response measures meet the WHO’s criteria for policy easing? - Petherick, A; Goldszmidt, R; Kira, B; Barberia, L (Blatnavik School of Government, 2020)
This paper brings together information about Brazil’s federal, state and state-capital Covid-19 response policies, mobile-phone mobility data, and original survey data, to assess whether the World Health Organization’s six criteria for evaluating readiness for easing response policies are met. We find that this is broadly not the case. Using OxCGRT for federal, state and some city governments, we report that subnational governments have enacted many of these policies, and that state-government policies have significantly affected behaviour (they impact all three available measures of citizens’ mobility). Although shifts in mobility have waned over time, during the period when policy stringency has been high (from mid-March until the end of May), these shifts have remained significant. Our survey of 1,654 people identified shortcomings in citizens’ understandings of how selfisolating people should behave: 95% of the populations of eight state-capital cities mistakenly believed that self-isolation means that you can leave the house to buy essential items. Correspondingly, recently symptomatic people were more likely than those who were unlikely to be contagious to leave home only once or twice within a fortnight. As reported elsewhere, testing and contact-tracing has been limited in Brazil (even though citizens have good knowledge of how to recognise Covid-19 symptoms), and economically vulnerable groups have seen the largest income reductions. We also find indications that having a high income predicts timely access to testing, and that income support has made up for at least half of the income losses of many of those receiving it. Privately schooled children and teenagers have received higher quality home education than their publicly schooled contemporaries. At the end of the paper we provide summaries reporting policy environments and survey results for eight state capitals – Fortaleza, Goiânia, Manaus, Porto Alegre, Recife, Rio de Janeiro, Salvador, and São Paulo.